Complications of femoral arterial lines in infants under 12 months - Benjamin David Carr; Sumer D Sebik; Clinton J Poling; Lindsay S Holland; Haley R Divis; Irene C St Charles; Anne E Baetzel; Samir K Gadepalli (Wolters Kluwer Medknow Publications, 2021)
Background: The risks of femoral arterial line placement in young children have been incompletely defined. We hypothesized that a low complication rate would be associated with ultrasound use. Subjects and Methods: Infants aged 0-12 months undergoing placement of a femoral arterial line at our institution over a 3.5-year period were identified through billing data, and their records were reviewed. Events concerning each line were recorded individually. Patients were excluded if there was incomplete documentation or if the line was in place for under 24 h. Demographics, information about line placement, and complications were recorded. Results: Three hundred and sixty-four femoral arterial lines were included. Eighty percent of lines were placed in the operating room, with the rest placed in the cardiac intensive care unit (ICU) (11%), the cardiac catheterization lab (6%), or the pediatric ICU (3%). Femoral artery occlusion occurred with 16% of lines placed, and limb ischemia in 6%. One patient had tissue loss. Occlusion was associated with lower gestational age at birth (44 [40-57] vs. 50 [41-60], P = 0.04), lower weight (3.7 [3.1-5.7] vs. 4.3 kg [3.3-6.2], P = 0.05), left-sided lines (52% vs. 66%, P = 0.05), placement in interventional catheterization lab (odds ratio [OR]: 3.28, confidence interval [CI]: 1.24-8.67, P = 0.02), >2 attempts (27% vs. 13%, P < 0.01), and catheter diameter (OR: 2.86, CI: 1.18-6.92, P = 0.02). Conclusion: Femoral arterial catheter placement in infants younger than 12 months resulted in a 16% rate of arterial occlusion at our institution, which was associated with low gestational age, larger catheter size, and left-sided lines but not ultrasound use, line duration, catheter length, use of anticoagulation, physician specialty, or physician training level.